2007
DOI: 10.1080/00207450600582033
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Hand and Foot Preferences

Abstract: 178C. BARUT ET AL.(22.11 ± 2.07). Of the right-handed men, 75.5% preferred the right foot, 7.1% the left foot, and 17.4% both feet. Of ambidextrous men, 44.0% preferred the right foot, 28.0% the left foot, and 28.0% both feet. Of left-handed men, 32.3% preferred the right foot, 56.9% the left foot, and 10.8% both feet. The differences between these percentages were found to be statistically significant. Of the right-handed women, 89.9% preferred the right foot, left foot 1.2%, both feet 8.9%, whereas 50.0% pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
0
20
0
7
Order By: Relevance
“…Since the first discoveries about the existence of lateralized functions in the human brain [1], they have been suggested right-left asymmetries to many of the higher cerebral functions, including motor control [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discoveries about the existence of lateralized functions in the human brain [1], they have been suggested right-left asymmetries to many of the higher cerebral functions, including motor control [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Strong right-handers may be defined as having a laterality index (LI) 1 greater than 75, and strong left-handers as having an LI lower than −75 on the Edinburgh Inventory, with all those in between considered ambidextrous (Knecht et al, 2000). In other studies, the cut-off for delimiting ambidexterity is set between +50 and −50 (Auer et al, 2009), between +40 and −40 (Li, Zhu, & Nuttall, 2003), between +20 and −20 (Cabinio et al, 2010) or between +15 and −15 (Barut, Ozer, Sevinc, Gumus, & Yunten, 2007) on the Edinburgh Inventory or a modified version of it. In another study, only participants who reported using 1 Laterality index (LI) is usually calculated as [number of right-hand responsesnumber of lefthand responses/total number of responses], and varies between 1 (completely right-handed) and -1 (completely left-handed), or between -100 and 100 if the LI is multiplied by 100.…”
mentioning
confidence: 99%
“…4 In a study by Barut et al, 90% of right-handed women between 18 and 42 years of age preferred their right feet compared with 76% in their male counterparts; for left-handed women, it was 79% who preferred their left foot compared with 57% in their male counterparts. 1 Among older adults, Kumar et al found that in a population of mostly males between 56 and 83 years of age, 94% had right-side dominance of both hand and foot, and that right-side dominance increased with increasing age. 9 Thus, dominance of ‘handedness’ appeared to operate in accord with dominance of ‘footedness’ for the vast majority of persons, although footedness may depend upon context of a specific foot task.…”
Section: Introductionmentioning
confidence: 99%